Phytoremediation potential of perennial grasses - Pandey, Vimal Chandra (Elsevier, 2020)
Phytoremediation Potential of Perennial Grasses provides readers with the knowledge to select specific perennial grass species according to site-specific needs. In addition, it demonstrates the potential opportunities for grass-based phytoremediation to yield phytoproducts, especially biomass-based bioenergy and aromatic essential oils as a green economy while in the process of remediating contaminated sites. The book brings together recent and established knowledge on different aspects of grass-based phytoremediation, providing this information in a single source that offers a cutting-edge synthesis of scientific and experiential knowledge on polluted site restoration that is useful for both practitioners and scientists in environmental science and ecology. --